CHILDREN OBESITY AND ITS CONSEQUENCES (CIPEEX, 2024)
CHILDHOOD OBESITY IS A DISEASE CHARACTERIZED BY AN INCREASE IN BODY FAT. IT IS CURRENTLY TREATEDAS ONE OF THE MAJOR PUBLIC HEALTH PROBLEMS WORLDWIDE WITH A SIGNIFICANT IMPACT ON POPULATIONHEALTH, AS IT CAN LEAD TO CHRONIC NON-COMMUNICABLE DISEASES SUCH AS SYSTEMIC ARTERIALHYPERTENSION (SAH), TYPE 2 DIABETES MELLITUS (T2DM), AND CARDIOVASCULAR DISEASES. IN BRAZIL,IT IS PRESENT IN DIFFERENT SOCIOECONOMIC GROUPS, BEING MORE COMMON IN THE UPPER SOCIAL CLASS.THIS CONDITION IS INFLUENCED BY SOCIOECONOMIC STATUS THROUGH INCOME, EDUCATION, ANDOCCUPATION AND RESULTS IN SPECIFIC BEHAVIORAL PATTERNS THAT CAN AFFECT METABOLIC RATE, CALORICINTAKE, AND ENERGY EXPENDITURE. OBESITY CAN BE DEFINED AND CLASSIFIED AS EXCESS FAT IN ALL BODYREGIONS, WHICH CAN BE CAUSED BY POOR EATING HABITS, ENDOCRINE-METABOLIC DISORDERS, OR GENETICALTERATIONS. OVERWEIGHT CAN OCCUR AT ANY STAGE OF AN INDIVIDUAL'S LIFE, BUT IT MAINLY APPEARS INTHE FIRST YEAR OF LIFE, BETWEEN 5 AND 6 YEARS OF AGE, AND DURING ADOLESCENCE. HOWEVER,INTERVENTION SHOULD BE CARRIED OUT AT ANY STAGE OF LIFE TO PREVENT COMPLICATIONS ARISING FROMEXCESS WEIGHT. THIS STUDY AIMS TO PROVIDE A THEORETICAL REFLECTION ON CHILDHOOD OBESITY ANDIDENTIFY THE GENERAL ASPECTS ASSOCIATED WITH THIS CONDITION, HIGHLIGHTING EPIDEMIOLOGICAL,ETIOLOGICAL, CONSEQUENCES, AND TREATMENT ASPECTS, CONSIDERING THE IMPORTANCE OF PHYSICALACTIVITY. IT IS A LITERATURE REVIEW CONDUCTED IN THE SCIELO AND GOOGLE SCHOLAR DATABASES, WITHSTUDIES RANGING FROM 2018 TO 2023. IT CAN BE CONCLUDED THAT CHILDHOOD OBESITY IS CURRENTLY ASERIOUS PUBLIC HEALTH PROBLEM WORLDWIDE. THERE ARE SEVERAL FACTORS THAT CAN LEAD TO OVERWEIGHT,INCLUDING GENETIC FACTORS, POOR NUTRITION, AND SEDENTARY LIFESTYLE. THEREFORE, THE MANAGEMENTAND PREVENTION OF CHILDHOOD OBESITY ARE IMPORTANT, AS IT CAN BE EASILY CONTROLLED IN THE VASTMAJORITY OF CASES THROUGH CHANGES IN EATING HABITS AND INCREASED PHYSICAL EXERCISE. IT IS KNOWNTHAT OBESITY IS RELATED TO VARIOUS COMPLICATIONS AND INCREASED CHILDHOOD MORBIDITY AND MORTALITY,AS WELL AS IN THE ADULT AGE GROUP. THEREFORE, IT IS OF UTMOST IMPORTANCE TO MAKE AN ACCURATEDIAGNOSIS AND PROVIDE PROPER TREATMENT, AS WELL AS TO IMPLEMENT PUBLIC POLICIES FOR THEPREVENTION OF CHILDHOOD OBESITY.
Keywords: Childhood obesity; Physical activity; Quality of life